Sensitivity analysis of queue‐based AQM over network parameters. Issue 4 (1st July 2019) - Patel, Sanjeev
Abstract : The comparative analysis of the active queue management (AQM) has been seen in the past work, while the comparative analyses for combined multiple output responses or performance parameters viz., throughput, delay, and loss rate are rarely seen in the literature. The comparative analysis using single variable comprising the output performance parameters has been attempted. The sensitivity of the network parameters over the throughput, delay, and loss rate for different AQM schemes has been measured. An attempt has also been made to stabilise the AQM algorithm that aims to achieve a low‐loss rate and a high throughput. The models for the stabilisation of queue size of random early detection (RED) based on the network parameter ma x p have been studied. The comparative performance analysis of existing stabilised models has also been presented with author's modified RED. The key idea is to modify the existing RED algorithm to achieve stabilisation in queue length at routers with the reduced loss rate as compared to RED.